The impact of COVID-19 on education - Giménez Armentia, Pilar; Viñado Oteo, Fernando (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this research, we analyze the effects that Covid-19 has had on the achievement of the 2030 Agenda and specifically on SDG4 on education as a conditioning factor for social and economic development. The methodology used has been a systematic review of the texts of the United Nations and other international organizations. The results and discussion address the setback that the pandemic has meant for the achievement of the SDGs, requiring the involvement of governments and organizations with more effective measures for greater access to quality education and a reduction in the digitalization gap.